2002
DOI: 10.1046/j.0007-1323.2001.02023.x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative enterococcal infection after treatment of complicated intra-abdominal sepsis

Abstract: Enterococci are frequently isolated from intra-abdominal infections of non-appendiceal origin and are often involved in postoperative infectious complications, particularly peritonitis. Empirical antibiotic therapy covering Enterococcus faecalis should be contemplated in some circumstances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
2
12

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(89 citation statements)
references
References 21 publications
3
71
2
12
Order By: Relevance
“…Several recent articles have attempted to better delineate the profile of patient populations at high risk of invasive enterococcal peritonitis and have suggested that empiric anti-enterococcal coverage in these patients may be beneficial [12,13]. Based on a selection of relevant articles, the present review attempts to summarise published evidence arguing in favour of empiric anti-enterococcal coverage in selected patient groups.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several recent articles have attempted to better delineate the profile of patient populations at high risk of invasive enterococcal peritonitis and have suggested that empiric anti-enterococcal coverage in these patients may be beneficial [12,13]. Based on a selection of relevant articles, the present review attempts to summarise published evidence arguing in favour of empiric anti-enterococcal coverage in selected patient groups.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have suggested that the presence of enterococci increases the infectious post-operative complication rate and even the risk of death [12,13]. For instance, Sitges-Serra et al [13] have looked at postoperative enterococcal infections after treatment of complicated intra-abdominal sepsis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Isolation of Enterococcus spp. is more common in patients with nosocomial intra-abdominal infections [17], and their isolation is a risk factor for treatment failure and death [61][62][63]. Inadequate empiric antimicrobial therapy is also a risk factor for treatment failure and death in patients with intra-abdominal infections [6,17,36] and is a strong predictor of mortality in critically ill patients with nosocomial pneumonia [64].…”
Section: Antimicrobial Therapy For Higher-risk Patients With Intra-abmentioning
confidence: 99%